The Struggle for Parliamentary Mandates for the 1786 Sejm in the Bracław Voivodeship - Filipczak, Witold (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The article focuses on the political situation in the Bracław voivodeship in the mid-1780s. In 1783, a change took place in structures of the royalist party in the south-eastern part of the Polish-Lithuanian Commonwealth. In the Bracław voivodeship, this led to the increased importance of the voivode of Ruthenia, Stanisław Szczęsny Potocki. The year 1784 saw a decline in the relations between Szczęsny Potocki and the Grocholski family previously in charge of the royalist activities in the Bracław voivodeship. In this conflict, the voivode of Ruthenia received the support of Stanisław August Poniatowski. Yet at the Grodno Sejm held in autumn 1784, Szczęsny Potocki stood in opposition to the king, which complicated matters even further. After that Sejm ended, Stanisław August took the course of arranging the royalist activities in the Bracław voivodeship sejmiks with the castellan of Bracław Marcin Grocholski, while simultaneously attempting to maintain a good relationship with Szczęsny Potocki. The list of endorsed Bracław deputies to the Sejm was agreed by Stanisław August with the voivode of Ruthenia at a meeting in Warsaw in late June and early July of 1786. There, the king accepted a number of candidates supported by Potocki, even though they had ties to the magnate opposition. Yet, during the election of Bracław deputies at the sejmik held in Winnica of 21 August 1786, the voivode of Ruthenia failed to honour the deal made with the king. The sejmik ended in a victory of Potocki’s supporters. At the 1786 Sejm, only one of the six Bracław deputies directly supported the adherents of the court.